In-Service English Teachers' Curriculum Literacy and Pedagogical Decision-Making in Lesotho Secondary Schools: The Contextual Role of Instructional Leadership - Nthatuoa Lephats’oe; Lineo Mphatsoane-Sesoane (Universitas Majalengka, 2026)
This study explores in-service English teachers' curriculum literacy and pedagogical decision-making in Lesotho secondary schools, while considering instructional leadership as a contextual factor influencing the enactment of classroom practice. While previous research has established links between teacher knowledge and student outcomes, there is limited qualitative evidence regarding how teachers interpret and enact the curriculum within their specific school contexts. Guided by Borg's theory of teacher cognition and informed by instructional leadership as a contextual lens, the study employed an interpretivist, qualitative, multiple-case study design. Data were generated through semi-structured interviews and non-participant classroom observations involving four purposively selected in-service English teachers and were analysed thematically. The findings indicate that teachers demonstrate sound curriculum literacy by employing learner-centred pedagogical strategies, including scaffolding, collaborative learning, multimodal instruction, the use of sample essays, and adapting instruction to learners' capabilities. However, translating curriculum literacy into effective pedagogical decision-making is constrained by contextual factors such as overcrowded classrooms, inadequate teaching resources, and time constraints. The study further reveals that instructional leadership provides an important contextual condition that can enable or constrain teachers' enactment of curriculum literacy, although the study’s primary focus remains teachers' cognition and pedagogical decision-making. The findings suggest that effective curriculum implementation depends not only on teachers' professional knowledge and beliefs but also on supportive instructional leadership that enables teachers to respond effectively to contextual challenges. The study concludes that strengthening instructional leadership in Lesotho secondary schools is essential for enhancing curriculum implementation, supporting teachers' pedagogical decision-making, and improving teaching and learning outcomes.